The Taming of the Shrewd: How Can the Military Tackle Sophistry, 'Fake' News and Post-Truth in the Digital Age?. Issue 1 (2nd January 2018) - Verrall, Neil; Mason, David
Abstract : Who can be believed and how should people act in a contemporary atmosphere of alternative facts, the rise of 'fake' information and post-truth politics? Neil Verrall and David Mason suggest that although these are not new concepts, the global speed and scale of information and discourse that military commanders need to address to communicate effectively in the current and future operating environments present new and challenging issues.